Analysis of Socio-Cultural and Religious Resilience in Sumbawa Regency - Jazadi, Iwan; Iskandar, Syaifuddin; Zuhri, Lahmuddin; Ardiyansyah; Haris, Andi; Arisanti, Ivon (Universitas Islam Negeri Madura, 2025)
This study aims to determine the socio-cultural and religious resilience index in Sumbawa Regency through social, cultural, and religious life indicators, as well as to determine the role of key stakeholders in facilitating the realization of this resilience. The design is a mixture of quantitative and qualitative research. Quantitative research includes data collection through a public perception questionnaire about the resilience indicators. Qualitative research includes the use of documentation, informal interviews and observations to explore the roles of key stakeholders in facilitating the realization of resilience in the regency. The study results show that the social, cultural, and religious resilience index in Sumbawa Regency recorded a score of 80.1 (high), indicating good and controlled conditions. The two dimensions with a very high category are religious tolerance (84.1) and equality in religion (83.1), while the others are in the high category, namely the social dimension (76.1), culture (78.5), and cooperation between religious communities (78.6). They indicate that all dimensions of resilience have room to improve to achieve optimal scores. The key stakeholders are vital in realizing socio-cultural and religious resilience in Sumbawa Regency. The collaboration and involvement of various group representatives in implementing activities contribute to realizing resilience in a pluralistic society in Sumbawa Regency.